(untitled) - The World Bank (Washington, D.C., 2008)
This new addition to the Little Data Book series presents at-a-glance tables for over 140 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency, sustainability, and applications.
Keywords: Developing countries,Phát triển quốc gia; Socio-economic aspects,Khía cạnh kinh tế xã hội